Optimal flight parameters of unmanned helicopter for tea plantation frost protection - Yongguang, Hu; Shengzhong, Liu; Wenye, Wu; Jizhang, Wang; Jianwen, Shen (International Journal of Agricultural and Biological Engineering, 2015)
To determine proper flight parameters of an unmanned helicopter for tea plantation frost protection, field experiments were conducted to study the impact of flight height, speed and interval on airflow disturbance and temperature rise around tea canopies based on the analysis and simulation of frost protection with a certain helicopter. The relationship between temperature rise after flight and the above flight parameters was established through a regression orthogonal experiment, based on which the optimal combination of flight parameters was obtained through the single-factor golden section method. The results showed that wind speed around tea canopies decreased with the increase of flight height when flight speed was constant. There was a multivariate linear relationship between temperature rise and flight parameters, and the sequence of flight parameters’ influence on frost protection effect was flight interval, flight height, flight speed. The optimal combination of flight parameters were flight height of 4.0 m, flight speed of 6.0 m/s and flight interval of 20 min. After the flight with the above parameters air temperature around tea canopies increased 1.6°C when background thermal inversion strength was 3.8°C. Keywords: thermal inversion, frost protection, unmanned helicopter, flight parameters, orthogonal experiment, single-factor golden section method, tea plants DOI: 10.3965/j.ijabe.20150805.1655 Citation: Hu Y G, Liu S Z, Wu W Y, Wang J Z, Shen J W. Optimal flight parameters of unmanned helicopter for tea plantation frost protection. Int J Agric & Biol Eng, 2015; 8(5): 50－57.